Cardiac Magnetic Resonance Imaging Right Ventricular Longitudinal Strain Predicts Mortality in Patients Undergoing TAVI - Schmid, Johannes; Kamml, Claus; Zweiker, David; Hatz, Dominik; Schmidt, Albrecht; Reiter, Ursula; Toth, Gabor G.; Fuchsjäger, Michael; Zirlik, Andreas; Binder, Josepha S.; Rainer, Peter P. (Frontiers in Cardiovascular Medicine, 2021)
Background: Right ventricular (RV) function predicts survival in numerous cardiac conditions, including left heart disease. The reference standard for non-invasive assessment of RV function is cardiac magnetic resonance imaging (CMR). The aim of this study was to investigate the association between pre-procedural CMR-derived RV functional parameters and mortality in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: Patients scheduled for TAVI were recruited to undergo pre-procedural CMR. Volumetric function and global longitudinal and circumferential strain (GLS and GCS) of the RV and left ventricle (LV) were measured. The association with the primary endpoint (1-year all-cause mortality) was analyzed with Cox regression. Results: Of 133 patients undergoing CMR, 113 patients were included in the analysis. Mean age was 81.8 ± 5.8 years, and 65% were female. Median follow-up was 3.9 [IQR 2.3–4.7] years. All-cause and cardiovascular mortality was 14 and 12% at 1 year, and 28 and 20% at 3 years, respectively. One-year all-cause mortality was significantly predicted by RV GLS [HR = 1.109 (95% CI: 1.023–1.203); p = 0.012], RV ejection fraction [HR = 0.956 (95% CI: 0.929–0.985); p = 0.003], RV end-diastolic volume index [HR = 1.009 (95% CI: 1.001–1.018); p = 0.025], and RV end-systolic volume index [HR = 1.010 (95% CI: 1.003–1.017); p = 0.005]. In receiver operating characteristic (ROC) analysis for 1-year all-cause mortality, the area under the curve was 0.705 (RV GLS) and 0.673 (RV EF). Associations decreased in strength at longer follow-up. None of the LV parameters was associated with mortality. Conclusions: RV function predicts intermediate-term mortality in TAVI patients while LV parameters were not associated with outcomes. Inclusion of easily obtainable RV GLS may improve future risk scores.